THE ROLE OF AI IN ENHANCING THE LEGAL EDUCATION AND RESEARCH - Pritam Singh, Amarjit Kaur (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2025)
The introduction of artificial intelligence (AI) into legal education is moving away from traditional methods of teaching, learning, and research in law. This paper explores the important role of AI in reshaping the way law students learn, research, and develop essential legal skills. The traditional method of studying law often relies on manual research, case analysis, and theoretical learning, which is time-consuming and sometimes limited by human capacity. With the integration of AI-powered tools, students are encouraged to access vast legal databases quickly and efficiently. Furthermore, AI supports personalized learning experiences through adaptive learning systems, which cater to individual student needs and improve engagement in their legal education. While enjoying all these benefits, to a certain extent, the use of AI in legal education and research also raises important challenges, mainly ethical concerns, where students are exposed too much to the technology and rely on it. This paper emphasizes that AI is not a replacement but a complement to traditional legal education and research. With the adoption of AI, students can develop more analytical, efficient, and innovative research skills, preparing them better for their future legal careers. It also gives learning institutions the opportunity to incorporate AI into legal education, hence becoming a dynamic learning environment that aligns with the evolving demands of the legal industry, ensuring students are well-equipped to meet future challenges.